Early Brain Imaging Shows Increased Severity of Acute Ischemic Strokes With Large Vessel Occlusion in COVID-19 Patients. Issue 11 (November 2020) - Escalard, Simon; Chalumeau, Vanessa; Escalard, Clément; Redjem, Hocine; Delvoye, François; Hébert, Solène; Smajda, Stanislas; Ciccio, Gabriele; Desilles, Jean-Philippe; Mazighi, Mikael; Blanc, Raphael; Maïer, Benjamin; et al.
Abstract : Background and Purpose: Reports are emerging regarding the association of acute ischemic strokes with large vessel occlusion and coronavirus disease 2019 (COVID-19). While a higher severity of these patients could be expected from the addition of both respiratory and neurological injury, COVID-19 patients with strokes can present with mild or none respiratory symptoms. We aimed to compare anterior circulation large vessel occlusion strokes severity between patients with and without COVID-19. Methods: We performed a comparative cohort study between patients with COVID-19 who had anterior circulation large vessel occlusion and early brain imaging within 3 hours from onset, in our institution during the 6 first weeks of the COVID-19 outbreak and a control group admitted during the same calendar period in 2019. Results: Twelve COVID-19 patients with anterior circulation large vessel occlusion and early brain imaging were included during the study period and compared with 34 control patients with anterior circulation large vessel occlusion and early brain imaging in 2019. Patients in the COVID-19 group were younger ( P =0.032) and had a history of diabetes mellitus more frequently ( P =0.039). Patients did not significantly differ on initial National Institutes of Health Stroke Scale nor time from onset to imaging ( P =0.18 and P =0.6, respectively). Patients with COVID-19 had more severe strokes than patients without COVID-19, with a significantly lower clot burden score (median: 6.5 versus 8, P =0.016), higher rate of multivessel occlusion (50% versus 8.8%, P =0.005), lower DWI-ASPECTS (Diffusion-Weighted Imaging–Alberta Stroke Program Early CT Scores; median: 5 versus 8, P =0.006), and higher infarct core volume (median: 58 versus 6 mL, P =0.004). Successful recanalization rate was similar in both groups ( P =0.767). In-hospital mortality was higher in the COVID-19 patients' group (41.7% versus 11.8%, P =0.025). Conclusions: Early brain imaging showed higher severity large vessel occlusion strokes in patients with COVID-19. Given the massive number of infected patients, concerns should be raised about the coming neurovascular impact of the pandemic worldwide.